50 simple things you can do to raise a child who loves science & nature - Brisk, Marion A. (Macmillan USA, 1998)
Simple, fun activities that can give 3- to 8-year-olds a head start on learning and life skills!How can you get your young child to love science and nature? This guide has fifty great answers! Created by a distinguished educator, this book presents fifty simple, fun, parent-child activities that can help kids develop lifelong interests and a love of learning. For each activity, easy-to-follow instructions tell parents what to do, what materials they'll need, how long the activity will take, and how to encourage the child to want to find out more.Marion A. Brisk directs the Chemistry Program at CUNY Medical School.